If $A,B$ non empty, upper bounded sets and $A+B=\{a+b\mid a\in A, b\in B\}$, how can I prove that $\sup(A+B)=\sup A+\sup B$?

  • 6
    $\begingroup$ The same way you show anything about a supremum: show that the right side is an upper bound of A+B, and then show that any other upper bound is larger. $\endgroup$ Sep 13 '10 at 17:25
  • 1
    $\begingroup$ I have a question, that , if we consider $A = (-1)^n $ & $B= 1/n$ . In this will $SUP A+B$ =$SUP A + SUP B$? $\endgroup$
    – Rkb
    May 30 '19 at 12:18

Set $x=\sup A$, $y=\sup B$. Given $a\in A, b\in B$ we have $a\le x, b\le y$ so $a+b\le x+y$ so it's an upper bound. Now take $\varepsilon > 0$ and find $a,b$ such that $a>x-\varepsilon/2, b>y-\varepsilon/2$ and you have $a+b > x+y - \varepsilon$. That suffices (since it means that every potential "smaller upper bound" $x+y-\varepsilon$ is not really an upper bound).

  • $\begingroup$ Why is your second line, not enough? (I'm asking why the first line is there). By uniqueness of the supremum, this says x + y = sup(A+B)? $\endgroup$
    – Travis62
    Jan 11 at 19:29

Show that $\sup(A+B)$ is less than or equal to $\sup(A)+\sup(B)$ by showing that the latter is an upper bound for $A+B$. Then show that $\sup(A)+\sup(B)$ is less than or equal to $\sup(A+B)$ by showing that $\sup(A+B)$ is an upper bound for $A+\sup(B)$ and that $\sup(A+\sup(B)) = \sup(A)+\sup(B)$.


The following proofs are based on Question 2 here. The nub is to prove two inequalities: $$\sup(A+B) \geq \sup A+ \sup B \tag{1}$$

$$\sup(A + B) \leq \sup A + \sup B \tag{2}$$

Proof of $(2)$:

By definition of $A + B$ and $\sup(A + B)$, for all $a \in A$ and $b \in B$,

$$\color{seagreen}{a + b} \color{seagreen}{\leq \sup (A + B)}.$$ Subtract $b$ from both sides:

$$a = \color{seagreen}{a + b} - b \color{seagreen}{\leq \sup (A + B)} - b.$$

Hence, if we fix $b \in B$, then $\color{seagreen}{\sup (A + B)} - b$ is an upper bound for $$\color{seagreen}{A + B} - B = A.$$

And so by definition of $\sup A$, for every $b \in B$, $$\sup A \leq \sup (A+ B) − b.$$ Rearrange the previous inequality: $\color{magenta}{b} \leq \sup(A +B) − \sup A$ for all $b \in B$.

Hence, $\sup(A +B) − \sup A$ is an upper bound for any $\color{magenta}{b}$.

By the definition of supremum, the previous inequality means: $$\color{magenta}{\sup B} \leq \sup(A + B) − \sup A \iff \sup A + \sup B \leq \sup(A + B).$$

Proof of $(1)$:

Since $\sup A$ is an upper bound for $A$, $a \leq \sup A$ for all $a \in A$. Then $b \leq \sup B$ for all $b \in B$. Hence $a + b \leq \sup A + \sup B$ for all $x \in A$ and $y \in B$. Hence, $\sup A + \sup B$ is an upper bound for $A + B$. Hence, by definition of supremum, $\sup A + \sup B \geq \sup(A + B)$.

  • $\begingroup$ Please correct me if I'm wrong, but I'm not entirely convinced by the latter half. $\sup (A+B)$ does not have to be part of the set $A+B$, right? So I'm not sure how your last statement holds - $\sup A + \sup B$ does not have to be $\ge A+B$ $\endgroup$
    – shreyasgm
    Oct 4 '17 at 1:22
  • $\begingroup$ @shreyasgm I may be wrong. How can I correct this pls? $\endgroup$
    – NNOX Apps
    Mar 21 '18 at 6:07
  • $\begingroup$ @TuckerRapu I improved your formatting, I hope that is alright. As an aside, why did you include the link at the top? $\endgroup$
    – user279515
    Aug 13 '18 at 18:28
  • $\begingroup$ @Brahadeesh No problem! That was thes ource. $\endgroup$
    – NNOX Apps
    Jan 12 '19 at 3:26
  • 1
    $\begingroup$ @TuckerRapu Oh, I see. Nice answer, btw. :) $\endgroup$
    – user279515
    Jan 12 '19 at 4:08

Another proof for $\sup(A + B) \geq \sup A + \sup B$.

Proof when $\sup A + \sup B$ is finite:

Posit $e > 0.$ Then there exists $a \in A$ and $b \in B$ such that $a > \sup A − \frac{e}{2}$ and $b > \sup B − \frac{e}{2}$. Then $a + b \in A + B$. Ergo, $$\color{seagreen}{\sup(A + B)} \geq a + b \color{seagreen}{> \sup A + \sup B - e} \implies \color{seagreen}{ \sup(A + B) > \sup A + \sup B - e }.$$ Since $e > 0$ is arbitrary, $\sup(A + B) \geq \sup A + \sup B$

Proof when $\sup A + \sup B$ is infinite:

Since the sets here are nonempty, the suprema here are not equal to $-\infty$, so we're not in danger of encountering the undefined sum $-\infty +\infty$. If $\sup A + \sup B = + \infty$, then at least one of the suprema, say $\sup B$, equals $+\infty$. Select some $a_0 \in A$. Then $$\sup(A+B) \geq \sup(a_0 + B) = a_0 + \sup B = + \infty,$$ so $\sup(A+B) \geq \sup(A) + \sup(B)$ holds in this case. (Source)


$$\forall ~~a\in A,~~b\in B, a\le \sup A~~ \text{and }~~b\le \sup B \implies a+b \le a\le \sup A +\sup B$$

hence $$\sup A +B\le \sup A +\sup B$$ Now we know there exist $a_n\in A$ and $b_n\in B$ such that $$\sup A=\lim_{n\to\infty} a_n$$ and $$\sup B =\lim_{n\to\infty}b_n$$

then $$\sup A+\sup B =\lim_{n\to\infty} a_n+\lim_{n\to\infty} b_n =\lim_{n\to\infty} a_n+b_n \le \sup A+B$$

whence $$\sup A+\sup B = \sup A+B$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.